Distinctive numbers of production systems functioning description - Pignasty, O.M. (Вопросы атомной науки и техники, 2007)
The production system of an enterprise is represented as the system with large quantity of elements, which are the objects of one's labour. The distinctive numbers of the production system are introduced by means of statistical mechanics. This approach gives the possibility of qualitative estimation of production processes functioning, sound selection of the corresponding equations set of macroscopic parameters balances for description of real production object. The estimation of the model selection should be interpreted as the qualitative one. The approach has the advantage of easy comparison of the results, corresponding to different microscopic models. Виробничу систему підприємства представлено у вигляді системи з великою кількістю елементів — предметів праці. За допомогою апарату статистичної механіки введено характерні числа виробничої системи. Цей підхід дає можливість провести якісну оцінку функціонування виробничого процесу, підібрати для опису реального виробничого об’єкту відповідну систему рівнянь балансів макроскопічних параметрів. Оцінку вибору моделі слід сприймати як якісну. Підхід має перевагу, що дозволяє легко порівнювати результати, що відповідають різноманітним мікромоделям. Производственная система предприятия представлена в виде системы с большим количеством элементов — предметов труда. Посредством аппарата статистической механики введены характерные числа производственной системы. Данный подход дает возможность провести качественную оценку функционирования производственного процесса, обоснованно подобрать для описания реального производственного объекта соответствующую систему уравнений балансов макроскопических параметров. Оценку выбора модели следует воспринимать как качественную. Подход обладает тем преимуществом, что позволяет легко сравнивать результаты, соответствующие различным микромоделям.